2015
DOI: 10.1111/hex.12416
|View full text |Cite
|
Sign up to set email alerts
|

Building intentions with the theory of planned behaviour: a qualitative assessment of salient beliefs about pharmacy value added services in Malaysia

Abstract: ObjectiveTo improve pharmaceutical care delivery in Malaysia, the Ministry of Health (MOH) had introduced the concept of value added services (VAS). Despite its reported convenience and advantages, VAS utilization rate is low in the country. The study aims to explore patients’ understanding, beliefs and expectations towards VAS in Malaysia using the theory of planned behaviour (TPB) as the theoretical model.MethodsA qualitative methodology was used whereby face‐to‐face interviews were conducted with 12 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 9 publications
1
29
1
1
Order By: Relevance
“…The conclusions from Phase 1 will assist the formation and formulation of research questions. 14 The qualitative study completed by Tan et al 15 showed clearly that five main themes emerged as significant predictors of intention which were attitudes, subjective norms, perceived behavioural control, knowledge and expectations in agreement with the TPB. This provides a strong impetus to proceed to Phase 2 of the study.…”
Section: Phase 1: Qualitative Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions from Phase 1 will assist the formation and formulation of research questions. 14 The qualitative study completed by Tan et al 15 showed clearly that five main themes emerged as significant predictors of intention which were attitudes, subjective norms, perceived behavioural control, knowledge and expectations in agreement with the TPB. This provides a strong impetus to proceed to Phase 2 of the study.…”
Section: Phase 1: Qualitative Explorationmentioning
confidence: 99%
“…Earlier work by Tan and colleagues' qualitative study suggests that knowledge and expectations also play a larger role than just predictors of intention but somehow indirectly affect the patient's perspectives through the TPB domains. 15 Thus, it is reasonable to posit that knowledge and expectations act as multiple mediators of each TPB construct of attitudes, subjective norms and perceived behavioural control. From Figure 1A, the total effect of X on Y is the c path for a relationship with no mediators.…”
Section: Mediation Analysis: the Role Of Knowledge And Expectationsmentioning
confidence: 99%
“…42 These studies by Tan and colleagues provide the policy maker with important conclusion regarding the implementation challenges of PVAS in Malaysia. [38][39][40][41] In particular, the results suggest that the influence of peers, friends and family plus the ease of which patients can use the services are the main predictors of adoption intentions. Generally, patient knowledge and their expectations can strengthen the relationship between intentions and cognitive perspectives.…”
Section: Discussion: Current Research and The Latest Findings For Malmentioning
confidence: 90%
“…The first is a series of interviews that aims to solicit and generate themes for analysis. 38 This is followed by the questionnaire development stage where a survey instrument is designed based on the thematic analysis gained from the qualitative stage as mentioned earlier. 39 Finally, the authors perform a final stage quantitative studies to capture the mediating effects of knowledge and expectations on intentions 40 and also to study how total cognitive perspectives (made up of subjective norms, perceived behavioural control and attitudes) can moderate the patient's intentions to adopt PVAS.…”
Section: Discussion: Current Research and The Latest Findings For Malmentioning
confidence: 99%
See 1 more Smart Citation